Supreme Court Review, 2005-2006. - Moller, Mark K. (Cato Institute, 2007)
In this annual review from the Cato Institute, Mark K. Moller and leading legal scholars analyze the 2005-2006 Supreme Court term, specificially the most important and far-reaching cases of the year, plus cases coming up. Now in its fifth edition, the Review is the first scholarly journal to appear after the term's end and the only one grounded in the nation's first principles, liberty, and limited government.